Enhancing Single-Cell Protein Yield Through Grass-Based Substrates: A Study of Lolium perenne and Kluyveromyces marxianus - Tianyi Guo; Joshua Bode; Katrin Kuka; Nils Tippkötter (Fermentation)
This study evaluated Lolium perenne press juice as a sustainable substrate for Single-Cell Protein (SCP) production using Kluyveromyces marxianus. Key fermentation parameters were systematically optimized, including microbial reduction, dilution ratios, temperature, and nutrient supplementation. Pasteurization at 75 °C preserved essential nutrients better than autoclaving, resulting in a 27.8% increase in biomass yield. A 1:2 dilution of press juice enhanced fermentation efficiency, achieving 20.2% higher biomass despite a lower initial sugar content. Cultivation at 30 °C enabled sustained substrate utilization and outperformed 40 °C fermentation, increasing final biomass by 43.4%. Nutrient supplementation with yeast extract, peptone, and glucose led to the highest biomass yield, with a 71% increase compared to unsupplemented juice. Press juice from the tetraploid variety, Explosion, consistently outperformed the diploid Honroso, especially when harvested early, reaching up to 16.62 g·L−1 biomass. Early harvests promoted faster growth, while late harvests exhibited higher biomass yield coefficients due to improved sugar-to-biomass conversion. Compared to a conventional YM medium, fermentation with L. perenne press juice achieved up to a threefold increase in biomass yield. These findings highlight the potential of grass-based substrates for efficient SCP production and demonstrate how agricultural parameters like variety and harvest timing influence both quantity and quality. The approach supports circular bioeconomy strategies by valorising underutilized biomass through microbial fermentation.